Quantitative contrast-enhanced ultrasonographic assessment of naturally occurring pancreatitis in dogs - Lim, Sue Yee; K., Nakamura; K., Morishita; N., Sasaki; M., Murakami; T., Osuga; N., Yokoyama; H., Ohta; M., Yamasaki; M., Takiguchi (Wiley-Blackwell Publishing, 2015)
Background: Quantitative contrast‐enhanced ultrasonography (CEUS) can detect pancreatic perfusion changes in experimentally induced canine pancreatitis. However, its usefulness in detecting perfusion changes in naturally occurring pancreatitis is unclear.